(untitled) (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2017)
The legislation on the establishment of the Registry of livestock animals is constantly evolving, and even pigs are subject to identification and registration. This is a relevant factor and guarantee for subsequent food chain, in a state like Italy that has a tradition of excellence in the world for food production processes with pork.